Effect of Feeding Probiotics and Milk Powder Supplemented Creep Ration on the Growth Performance and Efficiency of Feed Utilization in Pre-weaning Piglets - Tissopi, Monica; Bordoloi, J. P.; Hussain, Jakir; Ahmed, H. F.; Kro, Rajib (Indian Journal of Animal Nutrition, 2020)
The experiment was conducted to study the effect of creep feeding and its enrichment with probiotics and milk powder on the growth performance and efficiency of feed utilization in pre-weaning piglets. For the study 28 piglets of uniform size and body weight were selected from four litters of Hampshire sows of similar parity and allocated to 4 different dietary groups: T0 (fed conventional creep feed alone, control), T1 (fed 5% milk powder supplemented creep feed), T2 (fed probiotics supplemented creep feed added @1g per kg creep feed) and T3 (fed creep feed supplemented with 5% milk powder + probiotics @1g per kg creep feed) respectively, upto weaning age. The results of the body weights at 8th week of age was found to be significantly higher (P